LEARNING A FOREIGN LANGUAGE THROUGH TRAVELLING - Madina Khursandova (Journal of new century innovations, 2024)
This article deals with the structure and effective usage of learning foreign language. Moreover, the article describes the main differences of learning English as a usual way by searching or reading books and learning the language through travelling different sightseeing. The authors look into the language policy of universities through the academic mobility of students and teachers. Based on the research subject, the authors analyse relevant literature and use the empiric observation method and questionnaire of educational tourists. They also consider foreign language studying options at their native universities and compare them with the ways of studying at other universities in the context of educational tourism. The research shows the most popular forms of educational tourism for students studying foreign languages. It allows connecting travel experience and students' motivation to study. The paper will be helpful for researchers who try to optimise the educational process of learning languages by applying educational tourism and for people interested in improving their language skills and overcoming the language barrier.